CBDIR: Content Based Dental Image Retrieval using Deep Learning Techniques - Ramamurthy, B (International Journal of Advanced Science and Technology, 2020)
The advances in dentistry and its divisions have grown enormously in recent years. With these advances, the digital repository of dental radiography images also grown rapidly. To manage and retrieval of such digital storage images are highly critical due to scalability of the repository in day to day process. Moreover, In new era of dentistry images, intra-oral periapical X-rays, advanced imaging techniques like computed tomography (CT), cone beam computed tomography (CBCT), magnetic resonance imaging (MRI) and ultrasound have also played a pivotal role in diagnosing and treating issues related with dental. Digitization of these images makes process simpler and faster. Also facilitates image storage, manipulation (brightness/contrast, image cropping, etc.) and retrieval easier. This paper proposes a method to manage and retrieval of dental radiography images from highly scalable repository using deep learning techniques.